An Examination of the Latent Structure and Reproducibility of the Life Skills Scale for Sport in Botswana and Ghana - Malete, Leapetswe; Ricketts, Chelsi; Kim, Sehee; Tshube, Tshepang; Mphela, Thuso; Adamba, Clement; Ocansey, Reginald (Frontiers in Psychology, 2022)
Abstract With the growing interest in sport-based positive youth development (PYD) programs across the African continent, there is a need to establish suitable measures to evaluate the success of these programs in fostering PYD. The Life Skills Scale for Sport (LSSS) was recently developed as a sport-specific measure of life skills development. Despite its good psychometric properties among British youth sport participants, cross-cultural evidence indicates differences in the conceptualization of the eight factors measured by the LSSS. To determine the suitability of the LSSS for use in the African youth sport context, this study examined the latent structure and reproducibility of scores produced by the scale in a sample of youth sport participants from Botswana and Ghana. Cross sectional data from a sample of 495 youth athletes (male = 51.72%), aged 12–21 years (M = 16.76, SD = 1.58), from junior and senior secondary schools was used in this study. Confirmatory factor analysis and exploratory structural equation modeling were conducted, and conventional fit indices were used to assess model fit. Results on the original LSSS model indicated the need for model re-specification in the current sample. A re-specified LSSS, consisting of the original eight factors, but only 34 of the original 43 items, demonstrated improved fit and adequate internal consistency. Scores derived from the re-specified LSSS proved to be a valid estimate of life skills development in the current sample of youth sport participants. This has important implications for the utility of the LSSS in different cultures.